2023
DOI: 10.12913/22998624/157438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hard Oxides Reinforcing of Iron-Based MMCs on the Surface Topography Features after Finish Turning

Abstract: Metal matrix composites (MMCs) are widely used in various industrial applications. Various types of reinforcing particles are added to MMCs to improve their mechanical and functional properties. Optimal processing conditions for the elements manufactured from MMCs ensure the effi ciency of their use. This study describes the surface topography parameters of iron-based MMCs reinforced with graphite, alumina and zirconia nanoparticles depending on their percentage. The Simplex Lattice Design (SLD) method was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…The most uniform topography with the small areas with single high peaks is characteristic of materials under 50% strengthening. In comparison, significantly more surface defects are observed on the surfaces after finish turning of iron-based MMCs reinforced with graphite and hard nano-oxides [18]. Similar particularities were observed by Feldshtein et al [19].…”
Section: Surface Texture Changes After Turning Processsupporting
confidence: 70%
“…The most uniform topography with the small areas with single high peaks is characteristic of materials under 50% strengthening. In comparison, significantly more surface defects are observed on the surfaces after finish turning of iron-based MMCs reinforced with graphite and hard nano-oxides [18]. Similar particularities were observed by Feldshtein et al [19].…”
Section: Surface Texture Changes After Turning Processsupporting
confidence: 70%
“…In all outputs, it was observed that the results were better in the nanoparticle-added MQL environment. Maruda et al 55 machined Ti6Al4V titanium alloy in dry and MQL environments at different cutting speeds and feed rates at a constant depth of cut in this study. The effects of these parameters on surface topography were investigated.…”
Section: Introductionmentioning
confidence: 99%